Hot spots in Tcf4 for the interaction with beta-catenin. - Fasolini, M; Wu, X; Flocco, M; Trosset, J; Oppermann, U; Knapp, S (2003)
The interaction of beta-catenin with T-cell factor (Tcf) 4 plays a central role in the Wnt signaling pathway and has been discussed as a possible site of intervention for the development of anti-cancer drugs. In this study, we performed Ala-scanning mutagenesis of all Tcf4 residues in the Tcf-beta-catenin interface and studied the binding energetics of these mutants using isothermal titration calorimetry. Binding of Tcf4 was found to be highly cooperative. Single site mutations of most Tcf4 residues resulted in a significant reduction in binding enthalpies but in similar binding constants as compared with wild type Tcf4. Interestingly, this was also true for residues that are disordered in the reported crystal structures. The mutation D16A caused the largest reduction in binding constant (50-fold) accompanied by a large unfavorable enthalpy change (DeltaDeltaHobs) of +8 kcal/mol at 25 degrees C. In contrast, the mutation of the Tcf residues Glu24 and Glu28, which have been proposed as an interaction hot spot due to their location in a field of strong positive electrostatic potential on the beta-catenin surface (charge button), resulted only in a significant reduction of binding enthalpies, which were largely compensated for by unfavorable entropic contributions to the binding. Other mutations that significantly reduced Tcf binding constants were D11A and alanine mutations of the hydrophobic residues Leu41, Val44, and Leu48. The measured thermodynamic data are discussed with the available structural information of Tcf-beta-catenin crystal structures and allow us to propose possible sites for development of Tcf antagonists.